From Fragmented Practice to Rich Professional Learning: The Collaborative Work of Teachers of Learners With Deafblindness - Hartmann, Elizabeth S. (Frontiers in Education, 2020)
In this study, school professionals provided a rich context for understanding how collaboration can lead to learning when educating a child with deafblindness. Analysis of the collaboration of five professionals during an academic year showed that although they thought it was critical that they learn from each other, only one sub-set engaged in ways that led to rich learning opportunities. The findings from this study suggest that professional collaboration and learning, which is a hallmark of supporting learners with dual sensory loss, may be elusive even when it is a valued and mandated practice. In addition, professional learning more readily occurs when teachers are open to educating all children yet are also focused on how to best teach children with deafblindness.